Peningkatan Kompetensi Guru dalam Menyusun Rencana Pelaksanaan Pembelajaran Kurikulum 2013 Melalui Pendampingan di Gugus Sirih Gading UPT Dinas Pendidikan Pemuda dan Olahraga Kecamatan Kandangan - Sri Mulyani (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
The results of kindergarten teacher supervision were found in teaching teachers not yet making plans for daily activities, so learning activities did not run effectively. For this reason, action guidance is needed for the teacher to increase his competence in preparing the daily activity plan. The purpose of this study was to determine the improvement of kindergarten teacher competencies in preparing daily activities plans through ongoing guidance through mentoring in the Sirih Gading Cluster UPT Department of Youth and Sports Education Kandangan District Academic Year 2017/2018. The subjects of this study were all kindergarten teachers in the Sirih Gading UPT Cluster of the Department of Education, Youth and Sports, Kandangan District, totaling 18 teachers. With this school action research, it is expected that 75% of kindergarten teachers are able to plan their daily activities properly. The action is carried out with two cycles each cycle there are three meetings consisting of four stages, namely: planning, implementation, observation and reflection. The results of the action from cycle I to cycle II increased aspects of the competence of kindergarten teachers in preparing daily activities properly and correctly in the Sirih Gading Cluster UPT Department of Youth and Sports Education in Kandangan District 2018 in cycle I there were 6 teachers or 33% increased to 15 teachers or 85%. While its activity increased from 65% in the first cycle to 90% in the second cycle. Thus it can be concluded that through mentoring can improve the competence of kindergarten teachers in preparing daily activities plans in the Sirih Gading Cluster UPT Department of Youth and Sports Education in Kandangan District. Based on the research findings, suggestions can be made so that: (1) Teachers before carrying out learning to plan their daily activities properly and correctly, so that teaching and learning activities take place smoothly, effectively and efficiently and learning objectives are achieved. (2) Kindergarten Supervisors are advised to carry out ongoing guidance in preparing daily activity plans, so that Kindergarten teachers are able to prepare plans for day activities properly and correctly and Kindergarten Supervisors are advised to conduct further research on the skills of Kindergarten teachers in carrying out learning to find other aspects that are not yet revealed.